2018
DOI: 10.1002/qua.25647
|View full text |Cite
|
Sign up to set email alerts
|

Structural connectivity and formation mechanism of monometallic cluster fullerenes YCN@Cn (n = 68–84)

Abstract: Excited by the recently experimental reports of monometallic cluster fullerenes, we examined the electronic and geometrical properties of monometallic cluster fullerenes YCN@C n with size from C 68 to C 84 by density functional theory and statistical thermodynamic calculations. The calculations demonstrate that the thermodynamically favored isomers of YCN@C n are in good agreement with available experimental results. Morphology analysis shows that the lowest-energy YCN@C n species are structurally connected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…These Sc atoms can move along the surface of the growing carbon clusters and can be encapsulated within the cage. Our group systematically examined Sc 3 N@C n , 21 Sc 2 S@C n 22 and YCN@C n , 23 revealing that the energetically favored members are structurally interchanged through the insertion, extrusion, or rotation of a C 2 unit and thus suggest the crucial role of the C 2 unit in the formation of fullerenes and metallofullerenes. Experimentally, Kimura et al found that the formation of metal ion nuclei is crucial for the formation of metal-carbon clusters in metallofullerenes.…”
Section: Introductionmentioning
confidence: 99%
“…These Sc atoms can move along the surface of the growing carbon clusters and can be encapsulated within the cage. Our group systematically examined Sc 3 N@C n , 21 Sc 2 S@C n 22 and YCN@C n , 23 revealing that the energetically favored members are structurally interchanged through the insertion, extrusion, or rotation of a C 2 unit and thus suggest the crucial role of the C 2 unit in the formation of fullerenes and metallofullerenes. Experimentally, Kimura et al found that the formation of metal ion nuclei is crucial for the formation of metal-carbon clusters in metallofullerenes.…”
Section: Introductionmentioning
confidence: 99%
“…According to prior research, ,, the triplet states of U@ C s (15)-C 84 and U@ C 2 (8)-C 84 are the most energetically beneficial, while the singlet states of the other systems are more common in energy. Table shows the statistics over bond lengths, the HOMO–LUMO gaps of studied species, the relative energies of the three fullerene isomers and endohedral fullerenes as well as the sum of Mulliken charges on all carbon atom (ρ c ) for embedded derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that in some cases there is a strong interaction between the embedded metal and the carbon cage. 84 According to prior research, 41,85,86 the triplet states of U@ C s (15)-C 84 and U@C 2 (8)-C 84 are the most energetically beneficial, while the singlet states of the other systems are more common in energy. Table 1 shows the statistics over bond lengths, the HOMO−LUMO gaps of studied species, the relative energies of the three fullerene isomers and endohedral fullerenes as well as the sum of Mulliken charges on all carbon Compared with the original carbon cage and the shortest bond length of the C−C bond of the embedded derivatives increased, the longest bond length decreased, while the bond length of the YCN derivative changed more significantly.…”
Section: Methodsmentioning
confidence: 99%